1997
DOI: 10.1007/s002340050384
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of conventional and fast spin-echo sequences for the measurement of lesion load in multiple sclerosis using a semi-automated contour technique

Abstract: Changes on serial assessments of brain MRI lesion load are used for monitoring therapeutic efficacy in patients with multiple sclerosis (MS). We assessed the accuracy and reliability of conventional spin-echo (CSE) and fast spin-echo (FSE) sequences for measurement of lesion volume using a semiautomated contour technique. Cranial CSE and FSE examinations of 18 patients with secondary progressive MS were studied. The mean lesion load was slightly higher with the CSE sequence (p = 0.002). Intraobserver variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
2

Year Published

1998
1998
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
2
13
2
Order By: Relevance
“…The intra-observer COVs obtained in the present study were within the range of values previously reported [3, 4, 10, 16, 17]and we demonstrated that the performance of naive operators can be significantly improved for both enhanced and unenhanced T1-weighted MRI by a relatively short-term and cost-effective training. The lack of a significant training effect for PD-weighted images seems to be due to the good reproducibility obtained by one of the raters in the pretraining measurement sessions (COV 1.3%), whose value slightly worsened (2.0%) after the training.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The intra-observer COVs obtained in the present study were within the range of values previously reported [3, 4, 10, 16, 17]and we demonstrated that the performance of naive operators can be significantly improved for both enhanced and unenhanced T1-weighted MRI by a relatively short-term and cost-effective training. The lack of a significant training effect for PD-weighted images seems to be due to the good reproducibility obtained by one of the raters in the pretraining measurement sessions (COV 1.3%), whose value slightly worsened (2.0%) after the training.…”
Section: Discussionsupporting
confidence: 70%
“…Given the relatively small size of long-term LL changes, the effect of other factors influencing the reproducibility of serial measurements should be reduced as much as possible. Several previous studies evaluated the effects due to the use of multiple scanners [13], the quality of patient’s head repositioning within the scanner [14, 15]and the image acquisition schemes [16, 17, 18], and suggested several strategies to reduce them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fast spin-echo imaging was originally felt to be of equal sensitivity to conventional echo with improved imaging speed, quantitation of WMHI from fast spin-echo imaging has been recently shown to be less reliable. 33 Repeat WMHI determination from these images was therefore performed using operator guided tracing. This method has been previously shown to be reliable and correlates well with WMHI quantification by the mathematical method described above.…”
Section: Image Analysismentioning
confidence: 99%
“…TSE sequences provide the same image quality as conventional spin echo (CSE), but require significantly shorter acquisition times. Their sensitivity does not significantly differ from that of CSE in a variety of brain diseases, including cerebrovascular and white matter disorders [4,22,28].Abstract Fast fluid-attenuated inversion recovery (fFLAIR) is more sensitive that conventional or fast spin echo T2-weighted magnetic resonance imaging (MRI) for detecting lesions in the brain of patients with ischemic, inflammatory, or demyelinating diseases of the CNS. We investigated whether the use of fFLAIR also increases the sensitivity of brain MRI assessment in patients with systemic autoimmune disorders.…”
mentioning
confidence: 99%